2020
DOI: 10.2147/ijgm.s277273
|View full text |Cite
|
Sign up to set email alerts
|

<p>Perception Toward Quarantine for COVID-19 Among Adult Residents of Selected Towns in Southwest Ethiopia</p>

Abstract: Background COVID-19 is a global pandemic caused by a transmissible respiratory virus, SARS-Cov-2. Because it is a novel pathogen, limited information is available to characterize the spectrum of clinical illness, transmission efficiency, and the duration of viral shedding for patients with COVID-19. Quarantine is an important component of a multilayered strategy to prevent sustained spread of COVID-19 everywhere. The aim of this study was to assess public perceptions toward quarantine for COVID-19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…In addition, prisons and detention centers often lack sufficient hand washing areas, quarantine rooms, and personal protective equipment. 31 , 32 As a result, they are vulnerable to the transmission of COVID-19. Therefore, the aim of this research was to answer a research question, whether the correctional facilities were prepared and ready against COVID-19 pandemic in Bench-Sheko, Sheka, West Omo, and Keffa zones southwest, Ethiopia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, prisons and detention centers often lack sufficient hand washing areas, quarantine rooms, and personal protective equipment. 31 , 32 As a result, they are vulnerable to the transmission of COVID-19. Therefore, the aim of this research was to answer a research question, whether the correctional facilities were prepared and ready against COVID-19 pandemic in Bench-Sheko, Sheka, West Omo, and Keffa zones southwest, Ethiopia.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, prisons and detention centers often lack sufficient hand washing areas, quarantine rooms, and personal protective equipment. 31,32 As a result, they are vulnerable to the transmission of COVID-19. Therefore, the aim of this research was to submit your manuscript | www.dovepress.com…”
Section: Introductionmentioning
confidence: 99%
“… 44 This might be related to the study time gap, as the study conducted in South Korea was in 2015 so there is a high information difference related to quarantine compared to the current study. 43 In our study, the majority of participants reported that, during the movement restriction period, they always/often have spent quality time at home caring for their family (87.2%), making benefits of online media (89.6%), doing productive things for the family such as cooking, cleaning, etc. (85.5%), or obeying their religion (71.2%).…”
Section: Discussionmentioning
confidence: 67%
“…This finding is similar to that in Southwest Ethiopia, where only 52.3% reported a positive response toward quarantine. 43 Training people to understand the reason for quarantine might increase belief in its effectiveness and thus, their compliance with quarantine. 43 A study conducted in South Korea revealed that most of the participants believed quarantine was ineffective to control the Middle East respiratory syndrome (MERS) or even increases the risk of spreading MERS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation